YOUTH AND NATIONALISM IN AN INDONESIAN BORDER COMMUNITY - Yani, Andi Ahmad; Sangkala, Sangkala; Ramli AT, Muhammad; Burhanuddin, Agussalim; Ahmad, Badu (Indonesia Social Justice Network (ISJN), 2019)
The spirit of nationalism in youth groups is still in the question due to globalization awareness. This becomes a bigger question in border communities since they may have ?split national identity? in the daily life. In most studies of nationalism, traditional and liberal notion are highlightedTamir,1993; Druckman, 1994; Ignatieff, 1994; Shulman, 2002;). Traditional nationalism mainly refers to the love of the country affected by emotional attachment as native citizens. Conversely, liberal nationalism implies to a concept of nationalism based on the value of rationality and the desire for more independent thinking. Since there has not been many studies discussing youth nationalism in border areas, this research aims to identify the nationalism dynamic of youth groups in Sebatik Island, a border area with Malaysia?s territory in North Kalimantan Province. The study used survey and interview methods with 115 twelfth-grade students of four senior high schools as the subjects. The numbers of respondents represented four sub-districts in Sebatik Island. Using purposive sampling methods, the researchers selected students who have obtained the right to vote to address their political view. The result indicated that the youths of Sebatik Island tended to have traditional rather than liberal nationalism